La enseñanza de la métrica - Torre, Esteban (Rhythmica. Revista Española de Métrica Comparada, 2020)
Se parte en este trabajo de una regla de oro de la enseñanza, formulada por el filósofo español José Ortega y Gasset en su Misión de la Universidad –no se debe enseñar sino lo que se puede de verdad aprender–, y un consejo del metrista venezolano Andrés Bello en sus Principios de ortología y métrica de la lengua castellana –“conviene que el alumno aprenda a percibir por el oído la medida de los versos”–. Se analizan diversas pautas docentes en el terreno de la ciencia métrica. The point of departure for this study is represented by the golden rule of teaching, formulated by the Spanish philosopher, José Ortega y Gasset, in his Mission of the University ‒you should only teach that which can be truly learnt‒, as well as by the piece of advice provided by the Venezuelan metrist, Andrés Bello, in his Principles of Orthology and Meter in Castilian Spanish ‒“what is advisable is that the student learn to perceive the measure of poetic lines by ear”‒. Thereafter, a range of teaching models are analyzed in the field of the science of metrics.